2012
DOI: 10.1021/es202750t
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Fluoride from Aqueous Solution on Nano-Sized Hydroxyapatite: Examination of a Fluoridated Surface Layer

Abstract: Hydroxyapatite (Ca(10)(PO(4))(6)(OH)(2), HAP), both as a synthetic material and as a constituent of bone char, can serve as an effective and relatively inexpensive filter material for fluoride (F(-)) removal from drinking water in low-income countries. Fluoride uptake on HAP can occur through different mechanisms, which are, in principle, influenced by solution composition. Suspensions of HAP (2 g L(-1)) were equilibrated under controlled pH conditions (pH 6.5, 7.3, 9.5) at 25 °C for 28 d after the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 41 publications
10
63
0
1
Order By: Relevance
“…An alternative approach would be to use hydroxyapatite [HAp, Ca 10 (PO 4 ) 6 (OH) 2 ] as a possible fluoride adsorbent. Via ion exchange and/or dissolutionprecipitation reactions, HAp is able to remove fluoride to form stable fluorapatite [FAp, Ca 10 (PO 4 ) 6 F 2 ] [23], and can be obtained as bone char from food waste. FAp and HAp is stable in neutral pH range [6].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach would be to use hydroxyapatite [HAp, Ca 10 (PO 4 ) 6 (OH) 2 ] as a possible fluoride adsorbent. Via ion exchange and/or dissolutionprecipitation reactions, HAp is able to remove fluoride to form stable fluorapatite [FAp, Ca 10 (PO 4 ) 6 F 2 ] [23], and can be obtained as bone char from food waste. FAp and HAp is stable in neutral pH range [6].…”
Section: Introductionmentioning
confidence: 99%
“…22) However, the ground water in many areas has a very high F ¹ concentration. 22) HA has been reported to remove F ¹ by the exchange reaction of OH ¹ and F ¹ on the HA surface, 15) so the composition and shape of HA are important factors in F ¹ removal. The composition and the shape of HA, which is synthesized from calcium carbonate with phosphatecontaining solution, is changed significantly by the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Sternitzke et al reported that the removal of F ¹ occurs via the formation of FA at the HA surface, resulting in the formation of FA layer of few nanometers in thickness on the surface of HA. 9) Considering the report on the formation of FA layer with thicknesses larger than a, c-lattice constant values of HA, 22) the mechanism of "dissolution of HA and precipitation of FA" is considered to be the dominant factor in the removal of F ¹ . According to this mechanism, mainly the dissolution rate of HA contributes to the F ¹ removal process.…”
Section: ¹3mentioning
confidence: 99%